2020
DOI: 10.11609/jott.5552.12.13.16885-16890
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathological findings in a Dwarf Red Brocket Mazama rufina (Mammalia: Cetartiodactyla: Cervidae) attacked by dogs

Abstract: Capture myopathy is a common fatal syndrome in wild ungulates resulting from anthropogenic stressful events such as the capture or transport of specimens.  There are, however, few published data on this issue due to predator attacks.  The present report describes for the first time the capture myopathy syndrome in a Dwarf Red Brocket Mazama rufina following dog Canis familiaris attack.  Clinical signs included pale mucous with increase capillary refill time, tachycardia, tachypnea, hypertension, hypothermia, h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Previous studies show that domestic dogs are responsible for wildlife predation in Ecuador [ 49 , 50 ], and that attacks to wildlife are becoming more frequent, probably due to the increase in free-ranging dog densities [ 51 ]. However, until now, no data have been published on their involvement in livestock predation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies show that domestic dogs are responsible for wildlife predation in Ecuador [ 49 , 50 ], and that attacks to wildlife are becoming more frequent, probably due to the increase in free-ranging dog densities [ 51 ]. However, until now, no data have been published on their involvement in livestock predation.…”
Section: Discussionmentioning
confidence: 99%
“…Recent field observations using transects and camera traps in the Andean region of Ecuador have shown that the presence of feral dogs alters activity patterns and reduces the abundance of native mammals [ 47 , 48 ]. There is also data from dog attacks on wild species [ 49 , 50 , 51 ], but, to date, there are no published studies that have investigated whether dogs may also be negatively interacting with livestock. The Ministerio de Ambiente, Agua y Transición Ecológica (MAATE) is making efforts to manage human–wildlife conflicts through the training of its agents and the publication of a guide that explains how to determine if an attack on livestock was from an Andean bear, a jaguar, a puma, or a domestic dog [ 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, it may lead to myocardial myopathy and exercise-induced rhabdomyolysis, which is often documented in wild animals [41]. Other conditions that may affect CORT release may be related to intense short-term stress from transportation, immobilization, or predator attacks [42][43][44][45][46]. Stress also exerts an adverse effect on an animal's body weight, which is one of the most important determinants of reproductive success [47].…”
Section: Introductionmentioning
confidence: 99%
“…Due to current deforestation and hunting pressure, M. rufina is restricted to remnant vegetation patches with a downward population trend. This population downsizing has led the species to be classified as vulnerable by the IUCN (D. Lizcano & Alvarez, 2015; Lizcano et al, 2010), with the aggravating factor of depredation by feral dogs (Díaz et al, 2020; Doherty et al, 2017; Zapata‐Ríos & Branch, 2016).…”
Section: Introductionmentioning
confidence: 99%